Case series of dogs with blastomycosis managed with high-flow nasal oxygen therapy (2019–2023): 19 cases - Tarosky, Melanie; Haraschak, Jenica L.; Reinhart, Jennifer M.; Billhymer, Audrey (Frontiers in Veterinary Science, 2024)
Objective: To describe the clinical presentation, progression, treatment, and outcome of dogs with blastomycosis treated with high-flow nasal oxygen therapy (HFNOT).Setting: University veterinary teaching hospital Animals: Nineteen client-owned dogs with strongly suspected or confirmed blastomycosis treated with HFNOT.The medical records of dogs with strongly suspected or confirmed blastomycosis between October 2019 and May 2023 that received HFNOT were evaluated. Nineteen dogs were included. Nine dogs were started directly on high-flow nasal oxygen therapy. The remaining 10 dogs first received traditional oxygen therapy and were then transitioned to HFNOT 3-142 hours later. Of the 19 dogs, 1 survived to discharge from hospital, 12 were euthanized due to progression of disease, and 6 died during the hospitalization period.The prognosis for survival of dogs with severe blastomycosis requiring therapy beyond traditional oxygen methods was poor to grave in this population. This is the first known documented report of HFNOT use in dogs with confirmed or suspected blastomycosis.